Fabrication and mechanical properties of large‐scale SiC impeller via vacuum gelcasting and pressureless sintering. Issue 4 (7th April 2020) - Zhao, Zhanchong; Li, Xianhui; Zhang, Yong; He, Chenwei; Zhang, Xiaoxin; Liu, Huayan; Yan, Qingzhi
Abstract: Impeller is the key part of centrifugal pump to convey liquid. And combined with the engineering practice, we fabricated two types of open and semi‐open SiC ceramic impellers with diameter of 100 mm and 160 mm via gelcasting and pressureless sintering. B4C and C were used as the sintering additives and sprayed drying granulation method was adopted for the starting SiC powder processing. Given the size and shape complexity of impeller, the optimized pH value, dispersant content, and solid‐loading content for the fabrication of the SiC impellers were determined to be 10‐11, 0.8 wt%, and 40 vol%, respectively. For the open impeller, blade height, cover board thickness, drying shrinkage, and sintering shrinkage are 10.5 mm, 4 mm, 10.3%, and 21.3%, respectively. For the semi‐open ones, the corresponding parameters are 41 mm, 10 mm, 10.3%, and 21.3%, respectively. The average density of the two types of impellers is 3.15 g/cm3, and the mechanical properties of both impellers, including average hardness, flexural strength, compressive strength, and fracture toughness are 2478 HV, 436 MPa, 2093 MPa, and 3.17 MPa·m1/2, respectively. All variation coefficient values are smaller than 5%, which indicates a good uniformity in densities and mechanical properties of both the impellers.